PENINGKATAN MINAT BELAJAR DAN PEMAHAMAN KONSEP MATEMATIKA MELALUI PEMBELAJARAN QUANTUM LEARNING - Andini Dwima Chaerani (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to increase interest in learning and understanding mathematical concepts of Grade VIII A students of SMP Negeri 1 Garung by applying the Quantum Learning learning model. This type of research is a classroom action research (CAR) conducted on class VIII A as many as 32 students, consisting of 10 male students and 22 female students. Data collection techniques using observation, tests, questionnaires, and field notes. The instruments used in this study were the implementation sheet of the Quantum Learning model, the observation sheet of interest in learning, the questionnaire of interest in education, and the evaluation test for concept comprehension. Analysis of the data in this study used percentages and averages. Based on the results of the research, students' interest in learning mathematics has increased; this is indicated by students not sleepy, students are no longer ashamed to ask questions, and students are excited about doing assignments and presentations. Then an increase in understanding of mathematical concepts is shown by students being able to write the exact formula of the circumference and area of a circle, students can use procedures that are appropriate to what asked in the problem, and students can answer correctly.